Analisis Dampak Risiko Pertanian Komoditas Padi pada Gabungan Kelompok Tani (GAPOKTAN) Desa Purwasari - Rizky Julianto Perkasa; Prayoga Suryadarma (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The agricultural sector is one of Indonesia advantages as an agrarian country. Purwasari Villageis one of the villages located in Bogor which makes the agricultural sector as one of the sources ofincome that has a significant contribution to the regional economy. Fluctuations in productivity overthe past few months in Purwasari Village are thought to be due to internal and external risks. In thisstudy samples were taken from the Farmer Groups and villager in Purwasari Village. The methodsused are Fishbone Analysis and Failure Mode Effect Analysis to determine the sources of risk andpriorities in risk mitigation by farmers based on impact analysis by determining the critical value ofeach factor. The results of the study stated that the average level of critical value of rice farming inPurwasari Village obtained from the weighting results was 242.7 with moderate-high levels. The riskfactors that have the highest risk values above average are pest disruption, erratic weather, access tocapital and the quality of human resources.